PENERAPAN PERFORMANCE PRISM, AHP DAN OBJECTIVE MATRIX SEBAGAI ALAT UKUR KINERJA PADA UKM PENGOLAHAN IKAN DI KABUPATEN REMBANG - Agustina Widodo; Muhammad Sulton Adib (STIE Pelita Nusantara Semarang, 2018)
Measurement of the performance of UKM Karya Mina Putra uses more development of traditional accounting systems which only focus on the financial side. This is because financial measures can be easily done. Non-financial performance has been ignored because it is considered as something that is difficult to measure. Performance Prism performance measurement methods that provides comprehensive measurement and have a wide perspective so as to provide a realistic picture of the determinants of business success. Performance Prism not only measures the end result, but also the activities of the final outcome determinant. Thus, performance measurement can provide a clear and real picture of the actual condition of the company. Performance Prism is a performance measurement method that describes the performance of an organization as a construct of 3 (three) dimensions that has 5 (five) side fields, namely the stakeholder satisfaction, strategy, process, stakeholder capabilities and contributions. For the strategy perspective of 16 KPIs there are 2 KPI which needs to be improved. Understand the performance on the side of the process is still unsatisfactory because there are still 6 KPIs that are urgently needed to be repaired immediately. In the process perspective, achieving results is quite good. The most effective improvement is at the capability level.